Effects of changes in bird community composition and species abundance on plant reproduction, through pollination and seed dispersal. (12th April 2021) - Anderson, Sandra H.; Ladley, Jenny J.; Robertson, Alastair W.; Kelly, Dave
Abstract : The consequences of global bird declines on ecosystem function are gaining increasing attention. Here we consider the effects of changes in bird community composition and species abundance on reproduction for two endemic plant species in New Zealand. Birds service a relatively high proportion of the New Zealand flora as both pollinators and seed dispersers, and bird losses have been extensive during the 700 years since human colonization. We compare fruit set and seed removal for plants in reserves free of introduced predators, where seven endemic flower and fruit visiting bird species were present and relatively abundant, with plants outside these reserves where endemic bird species were absent or at lower abundance. The study plants, Dysoxylum spectabile and Pittosporum crassifolium, have both flowers and fruit visited by birds. Both species are also dioecious (a characteristic that has not been commonly associated with bird‐pollinated plants) and despite having mixed pollination systems, bird visits are essential for successful seed production. Outside introduced predator‐free reserves, the winter‐flowering D. spectabile was still visited by endemic pollinators and maintained pollination levels, despite a 59% decrease in endemic bird abundance. However, reduced endemic bird abundance was associated with a halving of pollination levels in P. crassifolium, which flowers in spring, as do other native and introduced flowering plants attractive to birds. The effect of altered bird species composition and abundance on seed dispersal was associated with a 74% reduction in seed dispersal for P. crassifolium . Additionally, undispersed seeds of P. crassifolium had lower germination, and higher pre‐dispersal seed predation, compared with dispersed seeds. We stress three important aspects of these results: (1) for some plant species, the same bird species perform both pollination and seed dispersal, (2) dispersal reduces pre‐dispersal seed predation, so that dispersal failure secondarily increases losses to seed predators, and (3) the effects of mutualism loss are not even across all species. Our results highlight that introduced species do not adequately replace endemic mutualists, which may be a particular problem for plant species with both bird‐visited flowers and fruit.